2021
DOI: 10.1177/1059601121994016
|View full text |Cite
|
Sign up to set email alerts
|

What Happens to Others Matters! An Intraindividual Processual Approach to Coworkers’ Psychological Contract Violations

Abstract: Drawing on recent research highlighting the dynamic and social properties of psychological contracts, we propose a framework that examines socially embedded triggers and their impact on psychological contract change. Our model accounts for the social context in which individuals’ sensemaking process about their employment relationship occurs. The model specifies how individuals make sense of coworkers’ psychological contract violation and integrate that information into the creation of a plausible convergent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 98 publications
(238 reference statements)
1
4
0
Order By: Relevance
“…The reasons are that (1) MNCs often select expatriates for their superior technical skills (Wang and Varma, 2022) and their high potential growth in the organization (Cerdin and Brewster, 2014), and thus, the organization's investment of resources in expatriates and treatment of expatriates upon repatriation are likely to attract the attention of others in the organization, (2) researchers have argued that expatriates are more prone to experience psychological contract breach upon repatriation than during other times in the employment relationship (Haslberger and Brewster, 2009) and several studies have shown that repatriates indeed talk about their experiences to other employees at both parent company and new work unit (Gregersen, 1992; Stroh et al. , 2000) and (3) supporting previous arguments and results from the repatriation literature, psychological contract theorists have argued and found that employees indeed rely on their informal social networks to understand their psychological contract beliefs and observing a coworker's psychological contract violation or hearing a coworker's disclosure of a psychological contract violation increases one's vigilance towards the organization (Costa and Coyle-Shapiro, 2021; Dabos and Rousseau, 2013).…”
Section: Theoretical Backgroundsupporting
confidence: 61%
See 1 more Smart Citation
“…The reasons are that (1) MNCs often select expatriates for their superior technical skills (Wang and Varma, 2022) and their high potential growth in the organization (Cerdin and Brewster, 2014), and thus, the organization's investment of resources in expatriates and treatment of expatriates upon repatriation are likely to attract the attention of others in the organization, (2) researchers have argued that expatriates are more prone to experience psychological contract breach upon repatriation than during other times in the employment relationship (Haslberger and Brewster, 2009) and several studies have shown that repatriates indeed talk about their experiences to other employees at both parent company and new work unit (Gregersen, 1992; Stroh et al. , 2000) and (3) supporting previous arguments and results from the repatriation literature, psychological contract theorists have argued and found that employees indeed rely on their informal social networks to understand their psychological contract beliefs and observing a coworker's psychological contract violation or hearing a coworker's disclosure of a psychological contract violation increases one's vigilance towards the organization (Costa and Coyle-Shapiro, 2021; Dabos and Rousseau, 2013).…”
Section: Theoretical Backgroundsupporting
confidence: 61%
“…In other words, "what happens to others in the organization helps fill in the blanks" (Rousseau and Greller, 1994, p. 388). And employees also use these cues to guide their subsequent behaviors (Costa and Coyle-Shapiro, 2021). The foregoing discussion suggests that the effect of developmental assignment usage on employee willingness for expatriation consists of a combination of two different pathways (i.e.…”
Section: Expatriation and Repatriation As One Processmentioning
confidence: 99%
“…Subsequently, they will begin to perceive their organization to be breaching psychological contracts intentionally because firms with high reputations are, otherwise, supposed to uphold, not break, the promises made to their employees. Indeed, what happens to the psychological contracts of others in a work unit shapes focal employees’ job attitudes (Costa et al , 2021).…”
Section: Background Literature and Hypothesesmentioning
confidence: 99%
“…The influence of a supervisor’s perception of his/her own PCB on a focal employee’s PCB – job attitude relationship needs further exploration. Supervisors’ PCB begets a focal employee’s PCB with a negative influence on the latter’s work outcomes (Bordia et al , 2010; Costa et al , 2021; Shi and Gordon, 2020). However, we hardly know if supervisor PCB will positively or negatively moderate the focal employee job attitude when the latter experiences PCB independent of his/her supervisor PCB.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one of the most recent research developments focused on the comparison of the differential impact of algorithmic management vs. human agents on perception of breaches and later employees’ outcomes [ 20 ]. Finally, considering the third parties’ information and the coworkers’ cues regarding violation, Costa and Coyle-Shapiro [ 21 ] recently proposed that social influence on an individual’s fulfillment evaluation could affect focal individuals’ psychological contracts. Despite the updates of these theoretical models [ 6 , 15 , 18 , 21 ], some relevant topics about psychological contract breaches, psychological contract fulfillment, their measurement, the relationships with their consequences, and the potential moderator variables still remain unclear.…”
Section: Introductionmentioning
confidence: 99%